Pain‐releasing action of Platelet‐activating factor (PAF) antagonists in neuropathic pain animal models and the mechanisms of action. (27th January 2013) - Motoyama, N.; Morita, K.; Kitayama, T.; Shiraishi, S.; Uezono, Y.; Nishimura, F.; Kanematsu, T.; Dohi, T.
Abstract: Background: Platelet‐activating factor (PAF) has been implicated in the pathology of neuropathic pain. Previous studies reported that PAF receptor (PAF‐R) antagonists have varied anti‐allodynia effects by route of administration and nerve injury models in rats. Methods: The present study elucidated the effectiveness of PAF antagonists against neuropathic pain in four different models of peripheral nerve injury and provided insights into the mode of anti‐allodynia action. Results: PAF antagonists, TCV‐309, BN 50739 and WEB 2086 by intravenous (i.v.) and oral administration have potent and long‐lasting anti‐allodynia action in mice neuropathic pain models. Treatment with PAF antagonists before surgery delayed the initiation of allodynia until the effects of these treatments were abolished. Intrathecal (i.t.) injection of the PAF antagonists and siRNA against PAF receptor ameliorated allodynia. I.t. injection of the glycine receptor (GlyR)α3 siRNA reduced the anti‐allodynia effect of PAF antagonists. This evidence suggests that the anti‐allodynia effect of PAF antagonists is at least in part mediated by spinal relief of PAF‐induced dysfunction of GlyRα3. An analysis of the mode of anti‐allodynia action of TCV‐309 in vivo revealed a competitive action against PAF shortly after the injection of TCV‐309, converting to a non‐competitive action later. Conclusions: The present results revealed the effectiveness in anti‐allodynia of PAF antagonists in different nerve injury models, and the unique mode of action; long‐lasting anti‐allodynia effects mediated by spinal GlyRα3 with a competitive manner at the initial stage and the following non‐competitive manner of inhibition.